2015
DOI: 10.1002/2015ja021035
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric and geomagnetic disturbances caused by the 2008 Wenchuan earthquake: A revisit

Abstract: Previous works have shown that coseismic ionospheric disturbances (CIDs) after the tsunamigenic 2011 Tohoku earthquake (Tohoku EQ, Mw9.1) covered a vast area and were observed thousands of kilometers away from the epicenter. For the purpose of making a comprehensive comparison between powerful oceanic and inland EQs, we conduct a retrospective investigation of CIDs and geomagnetic responses to the 2008 Wenchuan EQ (Mw7.9) using a combination of techniques, total electron content, HF Doppler, and ground magneto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 64 publications
4
31
0
Order By: Relevance
“…Sudden surface perturbations due to an earthquake or tsunami can induce seismo-traveling atmospheric disturbances (STADs) in the Earth's atmosphere. The observation of the ground-based GNSS TEC is an efficient technique for monitoring and examining the horizontal component of the STADs (e.g., Zhao and Hao 2015 and reference therein). Liu et al (2019b) suggested that the dense ground-based GNSS receiver networks can be treated as space buoy arrays to monitor the atmospheric gravity wave induced by tsunami and earthquake.…”
Section: Surface Perturbationsmentioning
confidence: 99%
“…Sudden surface perturbations due to an earthquake or tsunami can induce seismo-traveling atmospheric disturbances (STADs) in the Earth's atmosphere. The observation of the ground-based GNSS TEC is an efficient technique for monitoring and examining the horizontal component of the STADs (e.g., Zhao and Hao 2015 and reference therein). Liu et al (2019b) suggested that the dense ground-based GNSS receiver networks can be treated as space buoy arrays to monitor the atmospheric gravity wave induced by tsunami and earthquake.…”
Section: Surface Perturbationsmentioning
confidence: 99%
“…The impulse onset is simultaneous, as observed by receivers spreading over a distance of more than 10,000 km; also, there is no strong latitude dependence since the receivers at different latitudes all observed the impulse (see the IPP positions listed in Figure ). These features are barely observed in the ionosphere, since most known ionospheric disturbances are latitude dependent and have finite propagating speed; hence, their traveltime is apparent when observed by space‐separated instruments [e.g., Hao et al , ; Zhao and Hao , ]. An exception is the TEC enhancement caused by a solar flare eruption that happens in the whole dayside ionosphere simultaneously [ Zhang and Xiao , , ; Tsurutani et al , ], but still, this effect should appear in the signals from all overhead satellites.…”
Section: Gps Tec Observationsmentioning
confidence: 99%
“…Coseismic ionospheric disturbances (CIDs) after the tsunamigenic 2011 Tohoku Earthquake (Tohoku EQ, Mw 9.1) were observed thousands of kilometers away from the epicenter. Zhao and Hao [53] conducted a retrospective investigation of the CIDs and geomagnetic responses to the 2008 Wenchuan Earthquake (Mw 7.9) using multiple observations of TEC, HF Doppler, and ground magnetometer. This is the very first report to present the CIDs recorded by different techniques at co-located sites simultaneously.…”
Section: Ionospheric Climatology and Structuresmentioning
confidence: 99%